The Use of Discovery Learning Models in Improving Student Learning Achievement in the Material My Ambition to Become a Pious Child at SD Negeri 088 Panyabungan - Rasmi; Gustina, Ida; Nasution, Kholidah; Harahap, Emi Novita (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2024)
This study aims to improve students' learning achievement in the material My Ambition to Become a Good Child through the application of the Discovery Learning model in class V of SDN 088 Panyabungan. This learning model was chosen because it can stimulate students' activeness in finding concepts independently, improve their understanding, and learning outcomes. With this approach, students are more involved in the learning process and are able to develop critical thinking skills and problem-solving skills. This study uses the Classroom Action Research method which is carried out in two cycles. Each cycle consists of the planning, implementation, observation, and reflection stages. Data collection was carried out through learning outcome tests, observations, and interviews with students and teachers. The results of the study showed a significant increase in student learning achievement, which was indicated by an increase in the average value and increased active participation of students in learning activities. Based on these findings, it can be concluded that the use of the Discovery Learning model can effectively improve student learning achievement. Therefore, this model is recommended as an alternative in learning to improve students' understanding and learning outcomes, especially in Islamic Religious Education material